PAI Paradigm Transformation: Synthesis of K.H. Hasyim Asy’ari's Tazkiyatun Nafs and R.A. Kartini's Humanism in Responding to the Digital Empathy Crisis - Andi Qadri Al-Aqsha; Fatiha Amila Sholihah; Eksani; Abdussyukur (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
Islamic Religious Education (PAI) currently focuses on cognitive aspects, often lacking preventive power in responding to the phenomenon of cyber delinquency among adolescents. Previous studies generally analyzed character education partially, leaving a gap in an integrated approach between spiritual ethics and emotional intelligence in the digital era. Qualitative research based on literature studies (library research) aims to formulate a resolution to the digital empathy crisis through a synthesis of the thoughts of K.H. Hasyim Asy’ari and R.A. Kartini. Content analysis was conducted on primary sources in the form of Adab al-‘Alim wa al-Muta’allim book and Habis Gelap Terbitlah Terang book. The research results confirm that the combination of these two thoughts produces a solid character foundation, namely tazkiyatun nafs (K.H. Hasyim Asy’ari), which functions as an inner filter for vertical emotional control, while humanism (R.A. Kartini) fosters horizontal empathy. Novelty of this study lies in the formulation of a balance between manners and empathy as a specific solution to manage the morality of students who are unruly and indisciplined in interacting in cyberspace. The implications of this research suggest that Islamic Religious Education should adopt a dialogic and exemplary approach to enhance students' moral resilience.